Analisis Kompetensi Pedagogik Guru Produktif di SMK Negeri 1 Tarakan - ., Mustari (Program Studi Magister Pedagogi, 2015)
Analisis Kompetensi Pedagogik Guru Produktifdi SMK Negeri 1 TarakanMustariPengawas SMK pada Dinas Pendidikan Kota TarakanEmail: mus_ari@ymail.comAbstract:This research used a descriptive quantitative research methods and qualitative methods. The results showed that the implementation of pedagogical competences of the productive teachers at SMK Negeri 1 Tarakan as stated in the Educational Minister Regulation No.16 of 2007 has been well implemented. The conclusion was based on the computed profile recapitulation average of productive teachers’ pedagogical competences at SMK Negeri 1 Tarakan of 3,79 and with a percentage of 75,77 %. The data were supported by data from interviews, observations and documentation studies. Especially for the competence of empoying reflective action to improve the quality of instruction and the aspect of conducting classroom action research to improve the quality of instruction for the subject matter were not significant. It was based on the value of computed recapitulation average score of 1,85 with the percentage of 36,92 %. The data were also supported with data obtained from several interviewed respondents.Keywords: pedagogic competences, productive teachersAbstrak:Penelitian ini menggunakan metode penelitian deskriptif kuantitatif dan metode kualitatif. Hasil penelitian menunjukkan bahwa pelaksanaan kompetensi pedagogik guru produktif di SMK Negeri 1 Tarakan sebagaimana terdapat dalam Permendiknas No.16 tahun 2007 sudah dilaksanakan dengan baik. Kesimpulan ini berdasarkan hasil rata-rata keseluruhan rekapitulasi profil kompetensi pedagogik guru produktif di SMK Negeri 1 Tarakan sebesar 3,79 dengan prosentase 75,77%. Data ini didukung oleh data hasil wawancara, observasi dan studi dokumentasi. Khusus untuk kompetensi melakukan tindakan refleksi untuk peningkatan kualitas pembelajaran pada aspek melakukan penelitian tindakan kelas untuk meningkatkan kualitas pembelajaran dalam mata pelajaran yang diampu masih kurang. Hal ini berdasarkan nilai pada rekapitulasi rata-rata skor sebesar 1,85 dengan prosentase 36,92%. Data ini dikuatkan juga oleh data hasil wawancara dengan beberapa responden.Kata kunci: kompetensi pedagogik, guru produktif